BACKGROUND IMPULSE ACTIVITY OF KONTRALATERAL DEITERS NUCLEUS NEURONS OF LABYRINTHECTOMIZED RATS (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Computer analysis of background impulse activity of neurons of left-hand lateral vestibular nucleus (LVN) of rats in norm and after unilateral labyrinthectomy (OL) on 2, 7, 12 and 17 days is carried out. It is shown, that for 2nd day after OL values of average frequency and factor of a variation of interspike intervals authentically raise (41.1±3,8 (Hz), 116.4±2.7 (%) at 34.3±2.0 (Hz), 61.7±6.1 (%) in norm). The next days experiment’s value of average frequency impulsation of kontralateral neurons of LVN remained within the limits of norm, except the 17th day of the experiment when the last decreased up to 26.3±2.4 (Hz). Features and functional value of the received results are discussed.
Keywords: unilateral labyrinthectomy; left-hand lateral vestibular nucleus; impulse activity of neurons